Agile processes in software engineering and extreme programming : 21st International Conference on Agile Software Development, XP 2020, Copenhagen, Denmark, June 8-12, 2020, proceedings /: 21st International Conference on Agile Software Development, XP 2020, Copenhagen, Denmark, June 8-12, 2020, proceedings. (2020) - Unknown
No abstract available